Determination of antioxidant activity and phenolic compounds in different Mexican craft beers - González Mendoza, Daniel; Tzintzun-Camacho, Olivia; Mendez-Trujillo, Vianey (Revista Colombiana de Investigaciones Agroindustriales, 2022)
The objective of the present study was to evaluate and compare the phenolic content (total phenols and flavonoids) and the antioxidant capacity of seventeen craft beers produced in Mexico. The results showed a considerable amount of content of total phenols and flavonoids in the styles Coffee Stout Imperial (362 mg GAE/L and 75 mg QE/L) and Stout Ale (299 mg GAE/L and 40.92 mg QE/L), followed by American Brown Ale (271 mg GAE/L and 27.35 mg QE/L), Brown Ale (211 mg GAE/L and 24.20 mg QE/L), and Dark (328 mg GAE/L and 20.94 mg QE/L). In contrast, the American Wheat Ale (65 mg GAE/L and 2.91 mg QE/L), Lager (102 mg GAE/L and 3.56 mg QE/L), and IPA (103.73 mg GAE/L and 3.75 mg QE/L) showed the lowest content of phenols and flavonoids. The antioxidant capacity is detected in all the beers evaluated, mainly in the Coffee Stout Imperial style beer (80%). In this study, different contents of total carbohydrates were observed according to the type of beer, with Coffee Stout Imperial, American Brown Ale, and Brown being the ones that presented the highest content of carbohydrates (24.25, 15.55, and 15.36 g/L, respectively) followed by the type of Pilsner beer. (13.60g/L). Finally, our study showed that the different styles of beers in Mexico presented different contents of polyphenols (phenols and flavonoids), antioxidant capacity, and carbohydrates. However, the Coffee Stout Imperial style beer showed the highest values ​​of the aforementioned parameters. Future studies should be carried out in the evaluation of the biological activity of the different styles of beers on nutritional parameters in the Mexican population.